THE EFFECT OF ONLINE COUNSELING USING PUZZLE AND POSTER MEDIA ON DENTAL CARRIES KNOWLEDGE - Mery Novaria Pay; Agusthinus Wali; Leny M. A. Pinat; Merniwati Sherly Eluama (JDHT Journal of Dental Hygiene and Therapy, 2023)
Background: Dental and oral health is an integral part of overall health that can affect a person's quality of life so that it becomes a very important concern in Indonesia's health development, especially in elementary school-aged children. One way to increase children's knowledge is through online counseling using puzzles and posters. Research objective: to determine the effect of online counseling using puzzle media and posters on dental caries knowledge in students of Naikoten State Elementary School, Kupang City. The research design used a Quasi Experiment with a nonequivalent control group research design. Sampling was saturated sampling. The research instrument used a questionnaire and the analysis used SPSS with the Wilcoxon and Mann-Whitney tests. The results of the study: there is an influence between the level of knowledge of students who are given counseling using puzzle media is greater than poster media. This is evidenced by the results of the Mann-Whitney test, which obtained a p-value of 0.001 <0.05. From the results of the above study it was concluded that there was an effect before and after online counseling using pulzze media and posters.